TINJAUAN GAUDIUM ET SPES TENTANG MARTABAT MANUSIA DALAM KASUS TERORISME - Vinsensius Rixnaldi Masut; Martin Candy Putra Nugraha Barut; Flavianus Muwa; Anton Sad Budi (Jurnal Masalah Pastoral, 2022)
This study aims to explain human dignity in the Gaudium et Spes review dealing with acts of terrorism that occurred in Indonesia. According to Gaudium et Spes, humans are the image of God who has a reason, conscience, and free will. This nature makes humans special creatures created by God. So humans are also called to love and respect each other's dignity as imago Dei. Based on this, acts of terrorism that result in the loss of another person's life are seen as crimes. In comparison, human life and death are only in the hands of Allah. The methodology used in this study is a qualitative method by conducting a critical reading of the Gaudium et Spes document on human dignity. This theme is then analyzed with the issue of terrorism that occurred in Indonesia. The findings of this study are that acts of terrorism are contrary to the teachings of the Church which upholds human dignity. This can be seen in human nature as the image of God and as a free and independent person.